2021
DOI: 10.1002/anie.202111829
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Imaging of Mitochondrial DNA Base Excision Repair Reveals Dynamics of Oxidative Stress Responses

Abstract: Mitochondrial function in cells declines with aging and with neurodegeneration, due in large part to accumulated mutations in mitochondrial DNA (mtDNA) that arise from deficient DNA repair. However, measuring this repair activity is challenging. We employ a molecular approach for visualizing mitochondrial base excision repair (BER) activity in situ by use of a fluorescent probe (UBER) that reacts rapidly with AP sites resulting from BER activity. Administering the probe to cultured cells revealed signals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Two unusual features of the reaction of CCVJ-1 with AP sites in DNA are (a) an extremely rapid reaction rate, with rate constants up to ∼400 M −1 sec −1 at neutral pH, and (b) a high degree of light-up of the rotor dye, which is dark in solution but gives up to 500-fold enhancement upon covalent binding with AP sites in DNA. These features enabled its use in imaging DNA repair in cells and tissues; it was found that the dye in DNA is highly photostable and can be observed with common fluorescein filter sets, and can also be imaged by two-photon excitation 10 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two unusual features of the reaction of CCVJ-1 with AP sites in DNA are (a) an extremely rapid reaction rate, with rate constants up to ∼400 M −1 sec −1 at neutral pH, and (b) a high degree of light-up of the rotor dye, which is dark in solution but gives up to 500-fold enhancement upon covalent binding with AP sites in DNA. These features enabled its use in imaging DNA repair in cells and tissues; it was found that the dye in DNA is highly photostable and can be observed with common fluorescein filter sets, and can also be imaged by two-photon excitation 10 .…”
Section: Resultsmentioning
confidence: 99%
“…Here, we report an in situ DNA labeling strategy for oligonucleotides as well as dsDNA that makes use of aldehyde-reactive rotor dyes, also known as universal base excision reporters (UBER) 9 , 10 , to trap AP sites resulting from excision of deaminated DNA bases. This methodology includes (i) chemical or enzymatic synthesis of a DNA strand containing one or more deaminated bases, (ii) base excision repair (BER) in which a bacterial glycosylase excises the deaminated base(s), generating reactive AP sites, and (iii) oxime bond formation between the AP site and light-up UBER dyes (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, despite recent reports showing that BER deficiency does not lead to increased mutation load in mtDNA or mtRNA in mice ( Kauppila et al, 2018 ), the fact that BER, as well as the nucleotide pool sanitizing enzymes MTH1 and deoxyuridine nucleotidohydrolase (dUTPase) that eliminates dUTP, exist in mitochondria indicate the importance of preventing and repairing base lesions in mtDNA ( Kang et al, 1995 ; Ladner and Caradonna, 1997 ; Ichikawa et al, 2008 ; Jun et al, 2022 ).…”
Section: Mitochondrial Maintenance: Mitochondrial Dynamics Clearance ...mentioning
confidence: 96%
“…In a recent study, CRISPR-Cas9 based gene editing was used to generate cells lacking DNA glycosylase OGG1 that removes 8-oxoG from DNA, or MTH1 that hydrolyses 8-oxo-dGTP to 8-oxo-dGMP to prevent its insertion into DNA. In vivo mitochondrial BER activity was measured in OGG1-and MTH1-deficient cells using a cell-and mitochondrial-permeable fluorescent probe that reacts with AP sites in mtDNA ( Jun et al, 2022 ). Following exposure of the cells to an exogenous oxidating compound, mitochondrial BER was greatly elevated in the MTH1 KO cell line demonstrating the importance of sanitizing 8-oxoG precursors in mitochondria.…”
Section: Mitochondrial Maintenance: Mitochondrial Dynamics Clearance ...mentioning
confidence: 99%
See 1 more Smart Citation